A META-ANALYSIS OF EDUCATIONAL DATA MINING ON IMPROVEMENTS IN LEARNING OUTCOMES. - ALSHAMMARI, IQBAL A.; ALDHAFIRI, MOHAMMED D.; AL-SHAMMARI, ZAID (College Student Journal)
A meta-synthesis study was conducted of 60 research studies on educational data mining (EDM) and their impacts on and outcomes for improving learning outcomes. After an overview, an examination of these outcomes is provided (Romero, Ventura, Espejo, & Hervás, 2008; Romero, et al., 2011). Then, a review of other EDM-related research published after 2008 (88 studies) was completed. Thirty-nine of those studies also offered an overview of EDM's impact on learning outcomes. In addition, 12 of the 39 studies investigated the efficacy of EDM for learning outcomes. EDM characteristics (i.e., tools, techniques, models, procedures, measures, and results) were examined in each of the 12 studies. Ninety-four of the total 148 studies showed positive results for EDM. Directions for future research are discussed.